EFFICACY OF OLIVE SEED POWDER AND DIATOMACEOUS EARTH AGAINST COWPEA WEEVIL (CALLOSOBRUCHUS MACULATUS FAB. ON STORED COWPEA - Dawud, A.M.; Audu, A.; Bukar, A.; Lawan M. B.; Kumshe, I. B.; Zubairu, M.; Goni, M.; Garga, M.S.; Mustapha, M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study evaluated the efficacy of olive (Olea europaea) seed powder and diatomaceous earth (DE) as eco-friendly alternatives to chemical insecticides for controlling cowpea weevil (Callosobruchus maculatus) on stored cowpea seeds. The experiment was conducted in the Entomology Laboratory of the Department of Agricultural Technology, Mohamet Lawan College of Agriculture, Maiduguri. The treatments consisted of four rates (0.0, 250, 500, and 750 g kg⁻¹) of both olive seed powder and diatomaceous earth. These were laid out in a Completely Randomized Design (CRD) replicated three times. Data were collected on adult mortality at 24, 48, and 72 hours after exposure. Results showed that both treatments significantly (P < 0.05) increased mortality of C. maculatus compared to the control. Olive seed powder caused progressive mortality with increasing dosage and exposure time, reaching 100% mortality at 750 g kg⁻¹ after 72 hours. Diatomaceous earth, however, performed more effectively, achieving 100% mortality at 500 g kg⁻¹ within 72 hours and at 750 g kg⁻¹ within 48 hours. The superior performance of DE is attributed to its desiccating action on the insect’s cuticle, leading to dehydration, while olive seed powder likely acted through bioactive secondary metabolites. This study confirms that both olive seed powder and diatomaceous earth are effective, low-cost, and environmentally safe materials for the management of C. maculatus in stored cowpea. The use of DE at 500 g kg⁻¹ is recommended for small-scale farmers due to its rapid action and affordability. Further studies on synergistic combinations of both materials are suggested to enhance sustainable storage pest management in tropical environments.